Biochemical Composition and Energy Strategy Along the Reproductive Cycle of Female Octopus vulgaris in Galician Waters (NW Spain) - Sieiro, Pilar; Otero, Jaime; Aubourg, Santiago P. (Frontiers in Physiology, 2020)
The common octopus, Octopus vulgaris, has a short life cycle, growing rapidly to maturity, spawning once, and characterized by an asynchronic oocyte development and a synchronic ovulation dying after breeding. This species has a protein and amino acid metabolism and it is usually defined as an income breeder. However, most biochemical studies lack an examination of the whole reproductive cycle, in particular the spawning process. We here studied the biochemical changes and determined the energy strategy along reproduction in female O. vulgaris, and found that proteins were the main energy reserve, primarily located in the body muscle when sexually maturing and decreasing during breeding. Lipids were also an important source of energy in the ovary and digestive gland and decreased during breeding too. By contrast, glycogen had a minor contribution to the energy content and was the unique compound that increased in spawning and post-spawning females. Additionally, the most abundant fatty acids (FA) in all tissues were 16:0, 18:0, 20:1n9, 20:4n6 (ARA), 20:5n3 (EPA) and 22:6n3 (DHA), with a clear predominance of long-chain polyunsaturated FA. The FA profile of mature ovaries was compared with other life stages finding similitudes with eggs, hatchlings and juveniles but considerable differences with paralarvae which showed higher DHA/ARA and EPA/ARA ratios. Therefore, we found important biochemical changes along the reproductive cycle that determined the energetic signature in each tissue, though no significant energy trade-offs between tissues were found, suggesting that, on the one hand, female O. vulgaris obtained energy directly from food accumulated simultaneously in the somatic and reproductive tissues during sexual maturation. However, an energy reallocation from somatic to reproductive growth would occur once vitellogenesis has started, so that the rate at which body growths would decrease in favor of ovary growth. On the other hand, during breeding, a general decrease in the energy content occurred in all tissues, so that the ovary would be responsible for the spawning success, whereas muscle tissues and digestive gland would independently supply the energy needed for the body maintenance safeguarding the female survival needed for the maternal care.